7SKiing on chromatin: Move globally, act locally. Issue 6 (2nd June 2016) - D'Orso, Iván
ABSTRACT: RNA polymerase II (Pol II) pausing at promoter-proximal regions is a highly regulated step in the transcription cycle. Pause release is facilitated by the P-TEFb kinase, which phosphorylates Pol II and negative elongation factors. Recent studies suggest that P-TEFb (as part of the inhibitory 7SK snRNP) is recruited to promoter-proximal regions through interaction with KAP1/TRIM28/TIF1β to facilitate 'on-site' kinase activation and transcription elongation. Here, I discuss features of this model and future challenges to further hone our understanding of transcriptional regulation including Pol II pausing and pause release.